Modern teacher role for increasing the students’ competence in pedagogical specialty - Abayeva, Gulnar (Opción, 2019)
The article considers the problem of formation of the teacher's image in the theory of psychological and pedagogical science. Very few young people are ready to practice pedagogy, working for a small teacher's salary and dealing with children. General scientific methods of research like generalization of pedagogical experience, questioning, method of system analysis and analytical review were used. A low percentage of young teachers in the school is one of the acutest problems of the Kazakh secondary education. However, young teachers are not only a reserve for the future, but also a target audience for innovative programs for schools.